2001
DOI: 10.1128/aem.67.6.2586-2595.2001
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Listeria monocytogenes Contamination Routes in Cold-Smoked Salmon Processing Plants Detected by DNA-Based Typing Methods

Abstract: The contamination routes of Listeria monocytogenes in cold-smoked salmon processing plants were investigated by analyzing 3,585 samples from products (produced in 1995, 1996, 1998, and 1999) and processing environments (samples obtained in 1998 and 1999) of two Danish smokehouses. The level of product contamination in plant I varied from 31 to 85%, and no L. monocytogenes was found on raw fish (30 fish were sampled). In plant II, the levels of both raw fish and product contamination varied from 0 to 25% (16 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(49 citation statements)
references
References 38 publications
0
45
2
2
Order By: Relevance
“…However, even though the pathogen has been detected and investigated in numerous processing plants, and has on certain occasions been found to persist in a plant over several years (Miettinen et al, 1999;Fonnesbech-Vogel et al, 2001), its ecology and adaptations in the processing plant environment still remain poorly understood. Furthermore, even though a recent report identified isolates with the ribotypes characteristic of ECII in Hispanic-style cheese plants (Kabuki et al, 2004), routine surveys of processing plants for L. monocytogenes have largely failed to document the presence and possible persistence of ECI and ECII isolates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though the pathogen has been detected and investigated in numerous processing plants, and has on certain occasions been found to persist in a plant over several years (Miettinen et al, 1999;Fonnesbech-Vogel et al, 2001), its ecology and adaptations in the processing plant environment still remain poorly understood. Furthermore, even though a recent report identified isolates with the ribotypes characteristic of ECII in Hispanic-style cheese plants (Kabuki et al, 2004), routine surveys of processing plants for L. monocytogenes have largely failed to document the presence and possible persistence of ECI and ECII isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also documented noticeable variations among plants in prevalence of L. monocytogenes, and of individual strain types (Dauphin et al, 2001;Fonnesbech-Vogel et al, 2001). One can speculate that different environmental conditions in the plants may select for certain strain types.…”
mentioning
confidence: 94%
“…Recently, it has been indicated that, many bacterial species are indigenous part of seafood, but they can also be found on the food processing surfaces, where they can subsequently contaminate the products. (8) During the processing of poultry carcasses, microbial contamination inevitably occurs as a consequence of the processing procedures used. At each stage of the process, ample opportunity exists for contamination of the carcass by microorganisms from the processing plant or by cross-contamination from other birds (2).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of the pathogen in raw salmon from Chile, Norway and the west coast of the US has been reported to be 8.0%, 21% and 29.5%, respectively (Hoffman et al 2003). In other studies the prevalence of L. monocytogenes has been found to be 7.8% for salmon in the USA (Norton et al 2001) and 7.4% in Denmark (Fonnesbech et al 2001). L. monocytogenes was isolated in rainbow trout from retail markets in USA from 54% of the 74 samples examined (Draughon et al 1999).…”
Section: Panda and Gargmentioning
confidence: 95%